2011
DOI: 10.1116/1.3570818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vacuum ultraviolet radiation on deposited and ultraviolet-cured low-k porous organosilicate glass

Abstract: Articles you may be interested inEffects of plasma and vacuum-ultraviolet exposure on the mechanical properties of low-k porous organosilicate glass J. Appl. Phys. 116, 044103 (2014); 10.1063/1.4891501Bandgap measurements of low-k porous organosilicate dielectrics using vacuum ultraviolet irradiation Appl. Phys. Lett. Effect of vacuum ultraviolet and ultraviolet irradiation on mobile charges in the bandgap of low-k -porous organosilicate dielectricsThe authors compare the effects of vacuum ultraviolet ͑VUV͒ ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…To complicate matters, further ESR studies have shown that additional defects can be created in low-k materials by downstream porogen removal and plasma etching processes that expose the low-k material to intense UV-VUV radiation, energetic ions, and chemically active radicals and neutrals. [123][124][125][126][127] These process-induced defects may not be present or dominant in the as-deposited material. Accordingly, understanding the exact nature of the electrical point defects in low-k materials fully integrated into actual metal interconnect structures is quite complicated and difficult to unravel.…”
Section: Introductionmentioning
confidence: 97%
“…To complicate matters, further ESR studies have shown that additional defects can be created in low-k materials by downstream porogen removal and plasma etching processes that expose the low-k material to intense UV-VUV radiation, energetic ions, and chemically active radicals and neutrals. [123][124][125][126][127] These process-induced defects may not be present or dominant in the as-deposited material. Accordingly, understanding the exact nature of the electrical point defects in low-k materials fully integrated into actual metal interconnect structures is quite complicated and difficult to unravel.…”
Section: Introductionmentioning
confidence: 97%
“…1,7 For low-k materials, it has been additionally shown that electrical traps and defects can be created by downstream porogen removal and plasma etching processes that expose the low-k material to intense UV-VUV radiation, energetic ions, and chemically active radicals. [17][18][19][20][21][22][23] Further studies have shown a direct correlation between trap/defect densities, leakage currents and TDDB failures. 18,24 Unfortunately, the current understanding of the chemical identity, structure, and energy level of electrical traps and defects in low-k materials is still limited.…”
mentioning
confidence: 97%
“…It must be mentioned although the density of trapped charges is relatively small, 3,7,8 that post treatment (e.g., UV exposure 12,13 and hydrogen annealing 17,18 ) might still be needed to make sure that there is no significant net charge generated due to photoemission. 13 As a result, the trapped charges within the bandgap of the dielectric are reduced, the defect states are passivated and electrical activity is mitigated 19 since trapped charges are shifted out of the band-gap of the low-k dielectric. 20 To prove this hypothesis, monochromatic photons between 7.6 and 8.9 eV were exposed on the samples.…”
Section: Effects Of Vacuum Ultraviolet Irradiation On Trapped Chargesmentioning
confidence: 99%
“…14 Higher photon energies were not selected since they could also generate large charge accumulation and affect the reliability of SiCOH films. 13 In addition, based on the relation between the wavelength of the VUV photons and their penetration depth in low-k dielectrics, 16 those photons with energies from 4.5 to 8.9 eV can easily penetrate through the dielectric layer. Finally, the normalized photoemission currents induced by different photon energies in these ranges are comparable.…”
Section: Effects Of Vacuum Ultraviolet Irradiation On Trapped Chargesmentioning
confidence: 99%
See 1 more Smart Citation